ICE ALGAE AS FOOD OF AN ANTARCTIC ICE-ASSOCIATED COPEPOD, PARALABIDOCERA ANTARCTICA (I. C. THOMPSON) (Ninth Symposium on Polar Biology) - ホシアイ, タカオ; タニムラ, アツシ; ワタナベ, ケンタロウ; HOSHIAI, Takao; TANIMURA, Atsushi; WATANABE, Kentaro (National Institute of Polar Research, 1987)
P(論文) To investigate the food source of an Antarctic ice-associated copepod, Paralabidocera antarctica (I. C. THOMPSON), the gut contents of the nauplius, copepodite and adult of this species were observed with a scanning electron microscope. Materials observed were collected in the ice-covered sea near Syowa Station (69°00'S, 39°35'E), Antarctica. Remains in the gut consisted of ice-associated diatom frustules, their fragments, and siliceous cyst-like organisms. This indicates that P. antarctica utilizes ice biota which consisted mainly of diatoms as the main food source. departmental bulletin paper